2016
DOI: 10.1007/s40675-016-0058-8
|View full text |Cite
|
Sign up to set email alerts
|

How Adult Caregiving Impacts Sleep: a Systematic Review

Abstract: Sleep disturbance can contribute to negative health outcomes. However, sleep complaints have been underrecognized and undertreated in caregivers of ill family members. This systematic review describes the impact of family caregiving on sleep and summarizes factors associated with sleep disturbance in caregivers. A literature search using PubMed, MEDLINE, PsycINFO, and CINAHL databases yielded 22 relevant research articles on family caregivers of ill adults. Analyses revealed that up to 76 % of caregivers repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
72
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 48 publications
(197 reference statements)
4
72
1
6
Order By: Relevance
“…An essential next step will be to evaluate associations of the Mediterranean diet as a predictor of sleep quality in a larger sample with sufficient power for pertinent subgroup analyses, so that potential moderating roles of race/ethnicity as well as menopausal and caregiving status can be evaluated. This is important given evidence that racial/ethnic minorities, post-menopausal women, and individuals with caregiving responsibilities are at increased risk for poor sleep [33,47,48]. Similarly, there is a need to evaluate potential sex differences in the relation between a Mediterranean diet and sleep.…”
Section: Discussionmentioning
confidence: 99%
“…An essential next step will be to evaluate associations of the Mediterranean diet as a predictor of sleep quality in a larger sample with sufficient power for pertinent subgroup analyses, so that potential moderating roles of race/ethnicity as well as menopausal and caregiving status can be evaluated. This is important given evidence that racial/ethnic minorities, post-menopausal women, and individuals with caregiving responsibilities are at increased risk for poor sleep [33,47,48]. Similarly, there is a need to evaluate potential sex differences in the relation between a Mediterranean diet and sleep.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that over 95% of advanced cancer caregivers experience sleep disturbance . Poor sleep may contribute to difficulties actually executing daily caregiving tasks and to increased caregiver burden . It has also been linked to anxiety, depression, and worse physical health in caregivers, as well as interference with the grieving process and difficulty returning to pre‐caregiving responsibilities after the patient's death …”
Section: Introductionmentioning
confidence: 99%
“…Shift work can disrupt the normal sleep-wake cycle and may increase the risk of health problems due to sleep deprivation, impaired sleep and fatigue (9,10). Furthermore, the prevalence of informal caregiving increases with age and research has shown associations of informal caregiving with sickness absence (11) and cardiovascular diseases (12), which may be partially mediated through high levels of stress and sleep disturbances (13)(14)(15)(16). However, the studies on the association between informal caregiving and sleep have rarely focused on participants in employment and their working conditions (16,17) although, eg, in the Europe and US, more than 50% of caregivers are employed (18,19).…”
mentioning
confidence: 99%
“…Furthermore, the prevalence of informal caregiving increases with age and research has shown associations of informal caregiving with sickness absence (11) and cardiovascular diseases (12), which may be partially mediated through high levels of stress and sleep disturbances (13)(14)(15)(16). However, the studies on the association between informal caregiving and sleep have rarely focused on participants in employment and their working conditions (16,17) although, eg, in the Europe and US, more than 50% of caregivers are employed (18,19). The few longitudinal studies on the association between informal caregiving and sleep disturbances among employees have produced inconsistent findings (20,21).…”
mentioning
confidence: 99%